Comprehensive Study of E-Bike Braking Dynamics: Modeling, Simulation, and Experimental Validation - Mutasim Salman; Shivam Chaturvedi; Wencong Su (IEEE Access)
The use of e-bikes has been on a rapid rise in the last few years. However, there are safety concerns associated with the use of these products that will limit their acceptance and the growth rate of their use. The objective of this work is to develop a physics-based model of bike braking dynamics that describes the braking performance under critical safety events (CSE) conditions. The CSE includes faults in braking system components. The early detection of these faults will facilitate sending a proactive alert to undertake proactive maintenance of the braking system are crucial to ensure safety and prevent injuries. In this paper, a model of the bike braking system during straight line maneuver is developed and validated. This model will be used for detection and isolation of braking system components faults as well as prediction of their failure. The model includes bike and passive rider dynamics, wheel dynamics, the mechanical brake linkages and the tire-road friction interaction including tire slip. The behavior of the mechanical brake linkages that relates the brake lever force, lever displacement and the brake pad normal force on the brake disk is modeled based on experimental tests. The model developed is tested through simulation and experimental acceleration test, where the bike is driven to achieve a desired speed and the brakes are applied at front and back levers with different intensities.